An Analysis of Financing Scheme Effect on Non-Performing Financing Asset at Islamic Banks In Indonesia - Fitrian Aprilianto (Falah: Jurnal Ekonomi Syariah, 2020)
This research aims to identify the impact of financing contracts on the risks confronted by Islamic banks measured by Non-Performing Financing (NPF). The data indicate that the value of NPF tends to annually increase along with a value close to the maximum limit set by Bank Indonesia (BI). The data of this study utilized secondary data in the form of monthly time series data in the period of January 2014 to December 2017 and cross-section data from the two types of Islamic Banking (Bank Usaha Syariah and Unit Usaha Syariah). The result indicates that the financing scheme which is based on the empirical scheme of profit-sharing schemes is proven to increase financing risk.